2004
DOI: 10.1370/afm.101
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial to Increase Cancer Screening Among Attendees of Community Health Centers

Abstract: BACKGROUNDWe assessed the effi cacy of the Cancer Screening Offi ce Systems (Cancer SOS), an intervention designed to increase cancer screening in primary care settings serving disadvantaged populations.METHODS Eight primary care clinics participating in a county-funded health insurance plan in Hillsborough County, Fla, agreed to take part in a cluster-randomized experimental trial. The Cancer SOS had 2 components: a cancer-screening checklist with chart stickers that indicated whether specifi c cancer-screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 74 publications
0
64
1
Order By: Relevance
“…Using the terms randomized trial and chart reminder and found 3 articles that assessed chart reminders to improve CRC screening. [33][34][35] In one of these studies, the use of office support systems, including chart reminders, increased the odds of completing mammography and FOBTs, 33 whereas in another study, use of a Comprehensive Annotated Reminder Tool did not increase FOBT but did increase many other services targeted by the tool. 34 Physician chart reminders did not improve CRC screening in another study of more than 20,000 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Using the terms randomized trial and chart reminder and found 3 articles that assessed chart reminders to improve CRC screening. [33][34][35] In one of these studies, the use of office support systems, including chart reminders, increased the odds of completing mammography and FOBTs, 33 whereas in another study, use of a Comprehensive Annotated Reminder Tool did not increase FOBT but did increase many other services targeted by the tool. 34 Physician chart reminders did not improve CRC screening in another study of more than 20,000 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that examine preventive CRC screening do so aiming to find the problem -e.g., patient barriers, [25][26][27][28][29][30] physician barriers, [5][6][7]31,32] system barriers [14,23,24,33,34] -and implement targeted interventions that solely impact CRC screening. These approaches, while successful to varying degrees, may be limited in their usefulness in applied practice settings for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…This grace period has been used in other studies. [23,24] For each eligible patient in the practice, a binary variable was created to indicate whether screening had occurred according to USPSTF/ACS recommendations (0 = no, 1 = yes).…”
Section: Methodsmentioning
confidence: 99%
“…This type of colour code which was administered in Cancer Screening Office Systems (Cancer SOS), an intervention designed to increase cancer screening in primary care settings serving disadvantaged populations in Hills-borough County had been found to be effective (Roetzheim et al, 2004).…”
Section: Discussionmentioning
confidence: 99%